(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
The article analyzes the social infrastructure of the villages of Surkhandarya region, its level of development and impact on the quality of life of the population. The author studied the state of education, medicine and other social services in rural areas, identified existing problems and ways to solve them. He also discussed the impact of the development of rural infrastructure on the economic development of the region and the well-being of the population. The results of the study include practical recommendations for the further development of rural infrastructure in Surkhandarya region.